CHANGES IN THE STRENGTH OF THE MUSCLE OF EXTREMITY THROUGH ROM (RANGE OF MOTION) EXERCISE IN STROKE PATIENTS IN THE WORKING AREA OF KARANGPLOSO HEALTH CENTER OF MALANG DISTRICT - Hanifatus Sabira Astrid; Sumirah Budi Pertami; Budiono Budiono (LPPM STIKes Karya Kesehatan, 2018)
Stroke is a disorder of the nervous system characterized by an acute attack resulting in paralysis of one side of the body persistently and causing death of nerve cells (neurons). Stroke can cause one of the effects of musculoskeletal disorders that is the reduction of muscle strength. One alternative therapy in the rehabilitation process in stroke patients is the Range Of Motion Exercise is a movement in the body segment occurs as a result of muscle contraction or force from the outside (external forces) that move the bone. This therapy is already known by therapists as well as health workers but in some hospitals The purpose of this study to determine the effect of ROM Exercise on changes in upper extremity muscle strength in stroke patients. The design of this study is a case study description with a sample size of 2 subjects of respondents. The observation result showed that muscle strength was> 3 in good category, showed a significant increase between muscle strength scale before and after done ROM Exercise caused by muscle contractions and frequent movements so that muscle mass increases and increases muscle strength and maintains joint mobility. It is expected that the results of this study, ROM Exercise can be used as health care workers as one of the effective treatment measures for stroke patients who experience weakness of muscle strength in the extremities and aims to speed recovery by appropriate and unscheduled techniques. Stroke merupakan gangguan pada sistem saraf ditandai dengan serangan akut / mendadak yang mengakibatkan kelumpuhan pada salah satu sisi badan secara persisten dan menimbulkan kematian sel saraf (neuron). Stroke dapat menimbulkan dampak salah satunya terjadi gangguan muskuloskeletal yaitu penururnan kekuatan otot. Salah satu terapi alternatif dalam proses rehabilitasi pada pasien stroke yaitu Range Of Motion Exercise merupakan gerakan pada segmen tubuh terjadi sebagai akibat kontraksi otot atau gaya dari luar (external forces) yang menggerakkan tulang. Terapi ini sudah dikenal oleh terapis maupun tenaga kesehatan namun pada beberapa rumah sakit. Tujuan penelitian ini untuk mengetahui pengaruh ROM Exercise terhadap perubahan kekuatan otot ekstremitas atas pada pasien stroke. Desain penelitian ini adalah studi kasus deskripsi dengan jumlah sampel 2 subjek responden. Hasil observasi menunujukan kekuatan otot yaitu >3 dalam kategori baik, menunjukan adanya peningkatan signifikan antara skala kekuatan otot sebelum dan sesudah dilakukan ROM Exercise disebabkan oleh kontraksi otot dan pergerakan yang sering dilakukan sehingga masa otot bertambah dan membuat kekuatan otot meningkat serta memelihara mobilitas persendian. Diharapkan hasil penilitian ini, ROM Exercise bisa dijadikan petugas kesehatan sebagai salah satu tindakan perawatan yang efektif untuk pasien stroke yang mengalami kelemahan kekuatan otot pada bagian ekstremitas dan bertujuan untuk mempercepat pemulihan dengan teknik yang sesuai dan terjadwal.